2020
DOI: 10.3892/ijo.2020.5121
|View full text |Cite
|
Sign up to set email alerts
|

Role of primary cilium in pancreatic ductal adenocarcinoma (Review)

Abstract: The primary cilium is a non-motile cellular structure extending from the apical membrane of epithelial cells that is involved in several processes due to its ability to receive and elaborate different signals. Ciliogenesis and its obliteration are essential for proliferating cells, and several signalling pathways are responsible for their regulation. In fact, the primary cilium is a central hub for numerous signalling pathways implicated in a variety of biological processes, such as the Hedgehog, mammalian tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…The connection between ciliogenesis, the formation of renal cysts, and the development of RCC is supported by a series of evidence published in the last 15 years [66][67][68][69][70][71][72][73]. Indeed, in 2004, Lolkema et al [74] firstly showed that VHL protein can modulate tubulin turnover, thus influencing cellular migration, polarization, and cell-cell interactions.…”
Section: Renal Cell Carcinomamentioning
confidence: 95%
“…The connection between ciliogenesis, the formation of renal cysts, and the development of RCC is supported by a series of evidence published in the last 15 years [66][67][68][69][70][71][72][73]. Indeed, in 2004, Lolkema et al [74] firstly showed that VHL protein can modulate tubulin turnover, thus influencing cellular migration, polarization, and cell-cell interactions.…”
Section: Renal Cell Carcinomamentioning
confidence: 95%
“…The clinical implications of ciliary genes in PDAC have been recently reviewed [177]. In particular, lower expression of ciliary-associated genes AURKA, PLK1, and NEK2 and higher expression of ciliary-related HDAC6 and INPP5E were associated with favorable prognosis.…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…In particular, the expression profile of AURKA has been associated with a negative prognostic index, as AURKA is overexpressed in tumors of higher histological grade. On the other hand, the overexpression of the cilioprotein INPP5E has been associated with a favorable prognosis [177].…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%